Processo de implementação de Ambiente Virtual de Aprendizagem (AVA) para disciplina Matemática Financeira na modalidade semipresencial EaD na instituição FAMOSP - Santos, Alexandre (2016)
Distance education (DE) is a topic that has been successfully growing on a national level, and because of that, it offers the opportunity to most people entering higher education by flexibility and mobility that this model provides. The objective of this study was to analyze some insights about Educational Designer in implementing the 20% of presentials disciplines to distance mode. In addition to addressing the theoretical aspects of the Educational Design, because in this new educational context arises the importance of the Educational Design, whose main characteristic is to be articulator between the direction of the institution, faculty and student body and being involved with the planning, development and use of educational resources, methods, techniques and activities to promote the teaching and learning according to the guidelines of the education program. The Financial Mathematics in FAMOPS It is the focus of the implementation of the online course, presenting the tools used by the Educational Designer applied within the Moodle, being synchronous and asynchronous, helps to monitor learning and encourage participation in individual and group activities